Awareness of nutrition problems among Vietnamese health and education professionals. (22nd March 2016) - Pham, Thi Hai Quynh; Worsley, Anthony; Lawrence, Mark; Marshall, Bernie
Abstract: Professionals who provide nutrition education and consulting to the public are encouraged to take into account the health, environmental and social contexts that influence health-related attitudes and behaviours in the population. This paper examined the awareness of shifts in population health outcomes associated with the nutrition transition in Vietnam among university nutrition lecturers, health professionals and school education professionals. Most of these professionals held accurate views of the current population health issues in Vietnam. However, they differed in their awareness of the seriousness of overweight and obesity. Although the majority indicated that the prevalence of obesity and non-communicable diseases (NCDs) had increased, nearly half believed that the government should complete its attempts to control undernutrition before trying to control obesity. More health professionals believed that food marketing was responsible for the growing prevalence of children's obesity, and more of them disapproved of the marketing of less healthy food to children. In contrast, the university nutrition lecturers were least aware of food marketing and the seriousness of obesity. Of the three groups, the university nutrition lecturers held less accurate perceptions of nutrition transition problems and their likely drivers. There is an urgent need for greater provision of public nutrition education for all three groups of professionals.